Boundary Layer Flows Theory, Applications and Numerical Methods - Ramachandra Prasad, Vallampati (IntechOpen, 2020)
Written by experts in the field, this book, "Boundary Layer Flows - Theory, Applications, and Numerical Methods" provides readers with the opportunity to explore its theoretical and experimental studies and their importance to the nonlinear theory of boundary layer flows, the theory of heat and mass transfer, and the dynamics of fluid. With the theory's importance for a wide variety of applications, applied mathematicians, scientists, and engineers - especially those in fluid dynamics - along with engineers of aeronautics, will undoubtedly welcome this authoritative, up-to-date book.